PENGARUH ACCELERATED LEARNING BERBASIS MUSIK BAROK TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN - Ahmad, Hariyatunnisa; Rukayah, Rukayah; Triyanto, Triyanto (Universitas Pendidikan Indonesia, 2019)
Abstract: Reading comprehension is flexible and sustainable cognitive and constructive process. Students 'understanding of reading content is still low, therefore there is need strategies to improve students' reading comprehension ability. One of strategy that can be used in reading comprehension learning is Accelerated Learning based on baroque music. Baroque music has no lyrics and neutral, besides that the baroque music have a strong influence on the ability to absorb information and memorize it. The purpose of this study was to determine differences in scores on the read comprehension ability of fifth grade students of elementary school before and after learning using Accelerated Learning based on baroque music. The design of this study uses nonequivalent control group with data collection techniques using test. The collected data were tested using Independent Sample t-test with a significance level of 5%. The results showed that there was a significant difference between the score of reading comprehension ability of fifth grade students of elementary school before and after learning using Accelerated Learning based on baroque music.Keywords: reading comprehension, learning strategy, Accelerated Learning, baroque musicÂ Abstrak: Membaca pemahaman adalah proses kognitif dan konstruktif yang fleksibel dan berkelanjutan. Pemahaman siswa mengenai isi bacaan masih belum optimal, oleh karena itu perlu adanya strategi untuk meningkatkan kemampuan membaca pemahaman siswa. Salah satu strategi yang dapat digunakan dalam pembelajaran membaca pemahaman adalah Accelerated Learning berbasis musik barok. Musik barok tidak memiliki lirik dan netral, selain itu musik barok memiliki pengaruh yang kuat pada kemampuan untuk menyerap informasi dan menghafalnya. Tujuan penelitian ini adalah untuk mengetahui perbedaan skor pada kemampuan membaca pemahaman siswa kelas 5 sekolah dasar sebelum dan sesudah belajar menggunakan Accelerated Learning berbasis musik barok. Desain penelitian ini menggunakan nonequivalent control group dengan teknik pengumpulan data menggunakan tes. Data yang terkumpul diuji menggunakan Independent Sample t-test dengan tingkat signifikansi 5%. Hasil penelitian menunjukkan bahwa ada perbedaan yang signifikan antara skor kemampuan membaca pemahaman siswa kelas 5 sekolah dasar sebelum dan sesudah pembelajaran yang menerapkan Accelerated Learning berbasis musik barok.Kata kunci: membaca pemahaman, strategi pembelajaran, Accelerated Learning, musik barok